La vulneración de los derechos laborales en las personas migrantes de la ciudad de Guaranda durante el periodo 2020-2021. - Núñez Apunte, Kenllya Dayana (2022)
Ecuador for several years, has been a place of welcome for foreign citizens, at the beginning of the year 2020 the entry of migrants to our country has increased, mainly migrants of Venezuelan nationality fleeing the economic crisis in their native country Venezuela. According to UNHCR statistics, 5.4 million people have left Venezuela and in Ecuador there are 523 thousand Venezuelans. The International Labor Organization (ILO) indicates that unemployment and the increase in poverty have led workers from several countries to seek work abroad, especially in sister countries such as Peru, Ecuador and Colombia. On the other hand, with the economic and labor crisis that our country is currently going through and the greater mobilization of foreign citizens, the hiring of migrant workers has increased, taking into consideration that under the acceptance of the hiring there is a waiver of labor rights. , in this case, Ecuadorian employers do not guarantee migrant workers good working conditions, with a minimum wage, lack of affiliation to social security as enshrined in the Constitution of the Republic of Ecuador. Migrant workers, for the most part, are undocumented persons who, despite their migratory status, our Constitution of Ecuador guarantees the enjoyment of fundamental, inherent and innate rights, which cannot be suppressed, eliminated, or limited by any employer, however, The reality is different, the labor rights of migrant workers are violated by the very fact that they are migrants and find themselves in a situation of need, they are even victims of xenophobia and discrimination, by disclosing information regarding their nationality, causing rejection, prejudice against migrant citizens. Regarding the remuneration of migrants, the acceptance of this condition is accepted by the migrant worker, it should be noted that legally the economic remuneration must not be less than the Unified Basic Salary, that is $425.00 (four hundred twenty-five US dollars), but as I had mentioned before, there is a waiver of rights, despite the fact that the Labor Code states that the rights of workers are inalienable. Undoubtedly there is taking advantage of the migratory circumstance to receive a remuneration lower than that determined by law, even the migrant worker accepts these conditions, since the economic 14 remuneration is greater than what they received in their country of origin. Likewise, many migrant workers do not enjoy the benefits of the law such as the thirteenth and fourth salary, vacations, overtime stipulated in the Labor Code. Therefore, the purpose of this research work is aimed at determining the various labor violations suffered by migrant workers and the legal effects that these violations entail, despite the fact that in our country all Ecuadorian and foreign citizens who live and they reside in Ecuador. The investigation will be carried out based on the doctrinal, legal, bibliographical analysis through the analytical and descriptive method, allowing to legally determine the possible effects and violations of labor rights of migrant workers in the city of Guaranda, surveys and interviews will also be applied as tools research for data collection.